One-Pot Synthesis of Pentasubstituted Pyrroles from Propargylic Alcohols, Amines, and Dialkyl Acetylenedicarboxylates; Tandem Amination, Propargylation and Cycloisomerization Catalyzed by Molecular Iodine - Bhunia, Nisith; Das, Biswanath (Synthesis, 2013)
A multicomponent one-pot synthesis of fully substituted pyrroles has been developed by the tandem reaction of amines, dialkyl acetylenedicarboxylates, and propargylic alcohols using iodine as a catalyst. The reaction was complete in three hours and afforded the products in high yields (75–88%). The method is simple, efficient, cost-effective, and metal-free.
Keywords: pentasubstituted pyrrole; tandem reaction; iodine; metal-free synthesis